Pengaruh Workaholic dan Work Engagement terhadap Kepuasan Kerja dengan Motivasi Kerja sebagai Variabel Intervening pada Sekretariat Daerah Kabupaten Bondowoso - Zainiah, Putri Yaqin; Thamrin, Moh; Herlambang, Toni (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The objective of this study is to evaluate the relationship between workaholism, work engagement, work motivation, and job satisfaction among the staff of the Bondowoso Regency Regional Secretariat. This research utilizes descriptive and quantitative research methods, along with statistical analysis to identify the relationships between the examined variables. The sample studied in this research comprises the entire staff of the Bondowoso Regency Regional Secretariat, totaling 165 individuals. Hypothesis testing was conducted with the assistance of WarpPLS 7.0. The results of hypothesis testing indicate that all variables examined in the hypotheses have a positive and significant influence. Furthermore, the analysis results also demonstrate that workaholism and work engagement have a significant indirect effect on job satisfaction through the mediating variable of motivation. Therefore, this research provides a significant contribution to understanding the relationships between workaholism, work engagement, work motivation, and job satisfaction among the staff of the Bondowoso Regency Regional Secretariat. The implications suggest that work motivation development programs can be effective strategies to enhance the level of job satisfaction among the staff. Keywords: Job Satisfaction, Work Motivation, Workaholism, Work Engagement.